Effect of Orally Administrated Acriflavine to larval of Red Tilapia (Oreochromis sp.) on Their Sex Ratio - Junior, M. Zairin; Nurlestiyoningrum, D.; Raswin, M. (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
Uncontrolled and excessive spawning of red tilapia (Oreochromis sp.) hinders fish growth to reach marketable size. Several techniques have been developed to produce monosex population to overcome the problem, such as sex reversal by hormonal administration. Androgen hormone is generally employed to meet the goal, although the use of this hormone had been restricted and its price is relatively high. Acriflavine is an alternative chemical and its effect on sex development toward male fish has been proved. In this study, acriflavine at dose of 0, 15, 25 and 35 mg/kg feed were fed to 10-day-old larvae for 6 weeks. Feeding of larvae by diet containing 17a-methyltestosterone (MT) at dose of 50 mg/kg was also observed as a comparison of acriflavin treatment. The results indicated that feeding of larvae by diet containing acriflavine 25 mg/kg (78.3%) and 35 mg/kg (79.0%) produced significantly higher percentage of male fish compared to 15 mg/kg and control. However, the result is still lower compared to that of MT treatment (99.2%). Acriflavine treatment had no effect on survival of red tilapia and survival rate was similar among treatments, ranged from 91.7% to 95.0%. Keywords: red tilapia, Orechromis sp., monosex, acriflavine ABSTRAK Pemijahan tak terkontrol dan berlebih pada ikan nila merah (Oreochromis sp.) menghambat pertumbuhan ikan untuk mencapai ukuran konsumsi. Beberapa teknik yang telah dikembangkan untuk menghasilkan ikan monosek sebagai solusi permasalahan tersebut antara lain dengan seks reversal menggunakan hormon. Secara umum, hormon golongan androgen digunakan untuk mencapai tujuan, namun penggunaannya mulai dibatasi dan harganya relatif mahal. Akriflavin merupakan bahan alternatif yang terbukti dapat mempengaruhi perkembangan kelamin ke arah jantan. Pada penelitian ini dilakukan pemberian akriflavin dengan dosis 0, 15, 25 dan 35 mg/kg pakan ke larva umur 10 hari selama 6 minggu. Sebagai pembanding juga dilakukan pemberian pakan yang mengandung hormon 17a-metiltestosteron dosis 50 mg/kg pakan. Hasil penelitian menunjukkan bahwa pemberian pakan yang mengandung akriflavin 25 mg/kg pakan (78,3%) dan 35 mg/kg pakan (79,0%) menghasilkan ikan jantan dengan persentase lebih banyak dibandingkan dengan perlakuan 15 mg/kg (72,46%) dan kontrol (58,37%). Namun demikian, hasil tersebut masih lebih rendah dibandingkan dengan perlakuan MT (99,2%). Perlakuan akriflavin tidak mempengaruhi kelangsungan hidup ikan nila merah dan tidak berbeda nyata dengan kontrol, berkisar antara 91,7-95,0%. Kata kunci: Nila merah, Orechromis sp., monoseks, akriflavin